2020
DOI: 10.3390/ijerph17155307
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of High-Speed Rail Projects: A Risk Coupling Model Based on System Dynamics

Abstract: Due to their characteristics and multiple objectives, high-speed rail (HSR) projects carry more complex risks than conventional projects and high correlation and conductivity are among the associated risk factors. Previous risk assessment frameworks for rail infrastructure have ignored the effects of risk interactions that inflate risk levels, namely, risk coupling effects. Based on a system dynamics method, this paper develops a risk coupling model for HSR project risk assessments. A risk factor list is estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…For example, Zhang et al [ 34 , 35 ] used the N-K model to analyze the coupling relationship among risk factors of a gas explosion, and concluded that the probability of gas explosion increases with the increase of the number of risk factors. Xue et al [ 36 ] built a risk coupling model for the risk assessment of high-speed railway projects based on the system dynamics method, which can identify the key coupling effects that increase risks, although their research applied the coupling model for analysis and studied the coupling mechanism of risk accidents. However, the analysis was based on a single risk factor, and the correlation between risks was not analyzed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Zhang et al [ 34 , 35 ] used the N-K model to analyze the coupling relationship among risk factors of a gas explosion, and concluded that the probability of gas explosion increases with the increase of the number of risk factors. Xue et al [ 36 ] built a risk coupling model for the risk assessment of high-speed railway projects based on the system dynamics method, which can identify the key coupling effects that increase risks, although their research applied the coupling model for analysis and studied the coupling mechanism of risk accidents. However, the analysis was based on a single risk factor, and the correlation between risks was not analyzed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As mentioned above, the reasons for the occurrence of risks are as important as their impact and lead to a full understanding of the risks. This concept exists in many risk assessment methods, but the majority of the methods usually focus on the assessment of an individual risk for the simplification of the model and do not pay attention to the causes of a risk, part of which can be due to the occurrence of other risks; this is especially effective when accurate risk assessment is important [14]. For instance, the approach of failure modes and effect analysis (F.M.E.A) includes a qualitative analysis of failure modes and seeks a quantitative analysis of their effects, in terms of the probability and effect, or the cause-and-impact tree just addresses the event points and determines the relationships between them [15].…”
Section: Literature Surveymentioning
confidence: 99%
“…Xue et al [14] developed a risk coupling model of the risk assessment of a high-speed railroad (HSR) project based on a system dynamics method. Sayyadi and Awasthi [27] described an integrated method for evaluating sustainable transport policies which was based on the system dynamics simulation and the analytic network process (A.N.P).…”
Section: Literature Surveymentioning
confidence: 99%
“…One primary goal of SD is to capture how components in a system interact with one another and how changes in one variable influence another over time [28,29]. Xue et al [30] proposed an SD-based risk model to assess risks of high-speed rail (HSR) projects. However, their proposed model has certain limitations, such as ignoring unavoidable subjectivity in experts' risk evaluations.…”
Section: Reviewing and Comparing Fuzzy System Dynamics And Fuzzy Cognitive Maps Capabilities To Model Construction Risk Management Systemmentioning
confidence: 99%